ANTI SHI’ISM IN INDONESIA: GENEALOGY, DEVELOPMENT, AND METHODS - Dede Syarif; Iskandar Zulkarnain; Dicky Sofjan (Harmoni, 2017)
The notion of anti Shi’sm is founded in many countries such as Saudi Arabia, Pakistan, Iraq, Syria, and some others countries in South East Asia: Indonesia, Malaysia and Brunei Darussalam. This paper discusses the origin, development, and methods of anti Shi’ism in Indonesian context. In order to understand the anti Shi’ism this also will cover the responses expressed by majority Sunni in general and in particular some religious group that continually show their anti Shia sentiment in vary of methods, including the anti Shi’ism in social media and the establishment of National of Anti Shia Alliance, known as ANAS (Aliansi Nasional Anti Shia).